2014
DOI: 10.3856/vol42-issue3-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of addition of Navicula sp. on plankton composition and postlarvae growth of Litopenaeus vannamei reared in culture tanks with zero water exchange

Abstract: ABSTRACT. The aim of this study was to evaluate the effect of the addition of Navicula sp. on plankton composition and postlarvae growth of Litopenaeus vannamei reared in culture tanks with zero water exchange systems. Four treatments were considered: zero water exchange (ZWE); ZWE with the addition of feed (ZWE-F); ZWE with the addition of Navicula sp. (ZWE-N) and ZWE with the addition of feed and Navicula sp. (ZWE-FN), all in triplicate. Shrimp of 17.7 ± 0.02 mg were stocked at a density of 2500 shrimp m -3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This group of organisms was reported in biofloc system by Emerenciano et al [61]. Moreover, in a postlarvae culture of L. vannamei reared in zero-water exchange, FerreiraMarinho et al [62] reported Cladocera abundance from 0.89 to 1.16 ind mL Nematoda is the other essential group in BFT. The body of these organisms is perfectly cylindrical, coated by a relatively thick noncellular cuticles secreted by the underlying epidermis.…”
Section: Zooplanktonmentioning
confidence: 70%
“…This group of organisms was reported in biofloc system by Emerenciano et al [61]. Moreover, in a postlarvae culture of L. vannamei reared in zero-water exchange, FerreiraMarinho et al [62] reported Cladocera abundance from 0.89 to 1.16 ind mL Nematoda is the other essential group in BFT. The body of these organisms is perfectly cylindrical, coated by a relatively thick noncellular cuticles secreted by the underlying epidermis.…”
Section: Zooplanktonmentioning
confidence: 70%
“…Though the pathogens cannot be eliminated in total from the culture system, their growth can be suppressed and kept under control by the beneficial bacteria, as established by this study. Recently, Ferreira-Marinho et al (2014) also reported that, the zero water exchange treatment showed better production parameters, indicating the benefits of the addition of Navicula sp. as a natural food source for L. vannamei postlarvae in zero water exchange systems.…”
Section: Food Conversion Ratio (Fcr)mentioning
confidence: 92%
“…Navicula sp. is the best feed for Vannamei shrimp compared to 28 other types of phytoplankton (Ferreira-Marinho et al 2014). This shows that in region of Masigit -Pawon Karst waters it has potential to develop Vannamei shrimp culture.…”
Section: Discussionmentioning
confidence: 87%